Parental perceptions surrounding polio and self-reported non-participation in polio supplementary immunization activities in Karachi, Pakistan: a mixed methods study - Asif Raza Khowaja; Sher Ali Khan; Naveeda Nizam; Saad Bin Omer; Anita Zaidi (The World Health Organization, 2012)
OBJECTIVE: To assess parent's knowledge and perceptions surrounding polio and polio vaccination, self-reported participation in polio supplementary immunization activities (SIAs) targeting children aged < 5 years, and reasons for non-participation. METHODS: The mixed methods study began with a cross-sectional survey in Karachi, Pakistan. A structured questionnaire was administered to assess parental knowledge of polio and participation in polio SIAs conducted in September and October 2011. Additionally, 30 parents of Pashtun ethnicity (a high-risk group) who refused to vaccinate their children were interviewed in depth to determine why. Descriptive and bivariate analyses by ethnic and socioeconomic group were performed for quantitative data; thematic analysis was conducted for qualitative interviews with Pashtun parents. FINDINGS: Of 1017 parents surveyed, 412 (41%) had never heard of polio; 132 (13%) did not participate in one SIA and 157 (15.4%) did not participate in either SIA. Among non-participants, 34 (21.6%) reported not having been contacted by a vaccinator; 116 (73.9%) reported having refused to participate, and 7 (4.5%) reported that the child was absent from home when the vaccinator visited. Refusals clustered in low-income Pashtun (43/441; 9.8%) and high-income families of any ethnic background (71/153; 46.4%). Low-income Pashtuns were more likely to not have participated in polio SIAs than low-income non-Pashtuns (odds ratio, OR: 7.1; 95% confidence interval, CI: 3.47-14.5). Reasons commonly cited among Pashtuns for refusing vaccination included fear of sterility; lack of faith in the polio vaccine; scepticism about the vaccination programme, and fear that the vaccine might contain religiously forbidden ingredients. CONCLUSION: In Karachi, interruption of polio transmission requires integrated and participatory community interventions targeting high-risk populations.